Adaptive Sliding Mode Control for Trajectory Tracking in Three-Wheeled Mobile Robots: Experimental Validation and Performance Analysis - Doan, Hoa Van (Universitas Muhammadiyah Yogyakarta, 2025)
This paper presents an adaptive sliding mode control approach (ASMC) designed for trajectory tracking of a three-wheeled mobile robot (TWMR), accounting for external disturbances and wheel slippage effects. First, the TWMR system model is converted into a dynamic form of the tracking error, and then a SMC is designed for this error model. The synthetic disturbance is approximated through an adaptive law, which helps the system maintain high stability. The results from simulating the controller on Matlab/Simulink software, as well as implementing the algorithm on the experimental TWMR model, have demonstrated the accuracy and efficiency of the proposed method.